2015
DOI: 10.4103/0976-7800.165590
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D, and bone mineral density with depressive symptoms burden in menopausal and postmenopausal women

Abstract: Background:The reported association between vitamin D level and loss of Bone mineral densitometry measurements (BMD) has been controversial.Objective:The objectıve of the current study was to determine whether low vitamin D level and BMD are associated with depresive symptoms as burden in Arab women during the menopausal and postmenopausal period.Design and Setting:A cross-sectional descriptive study design was used at the Primary Health Care (PHC) Centers in Qatar.Subjects:A multi-stage sampling design was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
(111 reference statements)
2
12
0
2
Order By: Relevance
“…The present research highlighted the importance of considering psychosocial factors, life style, and chronic disease management in providing health guidance for peri-menopausal women and postmenopausal women to enhance their quality of life and reduce the risk of depressive and stress symptoms, this consistent with the previous reported studies. [67891328] Furthermore, the current data suggest that there is a strong association between depression, anxiety and stress symptoms high rates in menopause and postmenopausal women: These findings are confirmative with some previous reported studies. [6789132122232425262728]…”
Section: Discussionsupporting
confidence: 92%
“…The present research highlighted the importance of considering psychosocial factors, life style, and chronic disease management in providing health guidance for peri-menopausal women and postmenopausal women to enhance their quality of life and reduce the risk of depressive and stress symptoms, this consistent with the previous reported studies. [67891328] Furthermore, the current data suggest that there is a strong association between depression, anxiety and stress symptoms high rates in menopause and postmenopausal women: These findings are confirmative with some previous reported studies. [6789132122232425262728]…”
Section: Discussionsupporting
confidence: 92%
“…Similar studies done in various part of the world demonstrated that BMD had no significant relation to serum 25(OH)D status [8,[20][21][22][23]. However, a few studies have shown a positive correlation of serum 25(OH)D levels and BMD [24][25][26].…”
Section: Discussionmentioning
confidence: 82%
“…[242526] Few studies have shown a positive correlation of serum 25(OH)D levels and BMD. [20222327] Vitamin D is a fundamental vitamin to maintain calcium level in the bone by increasing calcium absorption in the intestines, stimulating bone resorption by increasing number of osteoclasts, and maintain level of parathyroid hormone to stabilize serum calcium levels. [23]…”
Section: Discussionmentioning
confidence: 99%